2022
DOI: 10.1021/acsami.1c22676
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Magnetic and Superconducting Properties with the Strength of the Magnetic Proximity Effect in La0.67Sr0.33MnO3/SrTiO3/YBa2Cu3O7−δ Heterostructures

Abstract: The effect of the stacking sequence on magnetic and superconducting properties in La0.67Sr0.33MnO3 (LSMO)/YBa2Cu3O7−δ (YBCO) and LSMO/SrTiO3/YBCO heterostructures, which consequently affected the magnetic proximity effect (MPE), was investigated using spin-polarized neutron reflectivity experiments. The results established the intrinsic nature of MPE and its correlation with stacking sequence-dependent magnetic and superconducting properties in these oxide heterostructure systems. We found an increase in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The proximity effect in a superconductor (SC)/ferromagnet (FM) hybrid system has garnered great interest due to novel physics phenomena and the potential to exploit them in the promising avenue of superconducting spintronics. , The interaction between superconductivity and ferromagnetism in these systems leads to a competition between different order states and a reconstruction of structural coupling between the two layers, which projects a large impact on the superconducting performance by affecting the magnetization dynamics. Combination of a d-wave high-temperature superconductor YBa 2 Cu 3 O 7 (YBCO) and half-metallic manganites like La 0.67 Ca 0.33 MnO 3 (LCMO) or La 0.67 Sr 0.33 MnO 3 (LSMO) has been the most studied SC/FM oxide system. There are diversified results regarding the appearance of spin-triplet supercurrent and the interplay of superconductivity and ferromagnetism in these bilayer systems. Some studies were successful to improve the flux pinning and superconducting properties via generating spin-triplet supercurrent, and several recent experiments revealed that the electronic interaction, proximity effect, or a “magnetic dead layer” at the interface can affect the related properties. The properties and effects of the interfacial layer have been studied extensively, and some interesting results have been reported, such as the appearance of perpendicular magnetic anisotropy in an in-plane anisotropic LSMO film, the suppression of superconductivity, the appearance of spin-triplet supercurrent, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proximity effect in a superconductor (SC)/ferromagnet (FM) hybrid system has garnered great interest due to novel physics phenomena and the potential to exploit them in the promising avenue of superconducting spintronics. , The interaction between superconductivity and ferromagnetism in these systems leads to a competition between different order states and a reconstruction of structural coupling between the two layers, which projects a large impact on the superconducting performance by affecting the magnetization dynamics. Combination of a d-wave high-temperature superconductor YBa 2 Cu 3 O 7 (YBCO) and half-metallic manganites like La 0.67 Ca 0.33 MnO 3 (LCMO) or La 0.67 Sr 0.33 MnO 3 (LSMO) has been the most studied SC/FM oxide system. There are diversified results regarding the appearance of spin-triplet supercurrent and the interplay of superconductivity and ferromagnetism in these bilayer systems. Some studies were successful to improve the flux pinning and superconducting properties via generating spin-triplet supercurrent, and several recent experiments revealed that the electronic interaction, proximity effect, or a “magnetic dead layer” at the interface can affect the related properties. The properties and effects of the interfacial layer have been studied extensively, and some interesting results have been reported, such as the appearance of perpendicular magnetic anisotropy in an in-plane anisotropic LSMO film, the suppression of superconductivity, the appearance of spin-triplet supercurrent, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to intrinsic effects like interfacial strain, electron transfer from LSMO to YBCO, and possible orbital reconstruction, , some extrinsic factors like chemical intermixing, oxygen or cation vacancies, and structural defects can be named as some of the reasons for the formation of this layer . Considerable research has also been carried out to describe the characteristic of the interfacial layer and to modulate its effect on the overall superconductivity of the system. , …”
Section: Introductionmentioning
confidence: 99%
“…More recent work by Prada et al has also shown that the deposition sequence of YBCO/LSMO layers impacts on the formation of the depletion layers, [45] and other groups have shown that the delicate chemistry of the LSMO plays an important role. [46] The question of whether there is an induced moment in the superconducting interface warrants additional investigation. While some PNR studies did not directly detect any induced moment on the YBCO side, it is pointed out that the magnetic contrast is small, making this difficult to detect, and indeed, the data is compatible with a much smaller induced moment in the Cu, as proposed by Liu et al [41,42] We note that an induced moment in the superconducting layer can also potentially arise from the paramagnetic Meissner effect, or so-called "inverse proximity" effect.…”
Section: Superconductorsmentioning
confidence: 99%
“…[8][9][10][11] La 0.67 Sr 0.33 MnO 3 (LSMO) and YBa 2 Cu 3 O 7 (YBCO) are found to be good candidate materials for epitaxial growth with sharp interfaces due to their similar a/b lattice parameters. Various studies show exotic phenomena such as domain wall superconductivity, 12 triplet superconductivity, 13 change in vortex behavior, 14,15 etc. In a study by H.-Ye Wu et al 16 on superconducting/ferromagnetic multilayers, an enhancement of critical current density is reported in the low field regime, exhibiting the presence of a strong vortex pinning effect due to the presence of spin-vortex interaction.…”
Section: Introductionmentioning
confidence: 99%